Demographic differences in people living with HIV according to recruitment sources: comparison between health-care systems and social media networks. Issue 7 (2nd July 2020) - Hsiao, Yu-Hsiang; Lee, Ing-Kit; Lin, Te-Yu; Liao, Chia-Hung; Lee, Chen-Hsiang; Ku, Wen-Wei; Huang, Shie-Shian; Yu, Chia-Hui; Liu, Zhuo-Hao; Chiu, Yi-Chi; Lin, Yi-Hui; Chen, Nan-Yu
ABSTRACT: With the improvement of internet technology in health applications, the utilization of internet and social media as new survey methodologies and recruitment source for research participants have been encouraged, yet evidence of the feasibility in people living with HIV (PLHIV) study is still lacking. We conducted a cross-sectional survey to determine whether there are differences among PLHIV recruited from social media networks and health-care systems using an HIV stigma and discrimination questionnaire. The result revealed that PLHIV recruited from social media networks were younger, more sexually active, and had higher educational status and awareness of the country's HIV rights protection laws than those recruited from hospitals. By contrast, participants recruited from hospitals were more diverse regarding key population compositions, had lived with HIV for a longer duration, had a higher prevalence of concomitant physical disabilities than those recruited from social media networks, and fit Taiwan PLHIV characteristics described by 2016 census from Taiwan Centres for Disease Control. We conclude that sampling bias exists when utilizing social media networks for PLHIV studies.